Evaluation of ruminal motility in cattle by a bolus-type wireless sensor - ARAI, Shozo; ITOH, Toshihiro; TAKAHASHI, Yuji; KIMURA, Kumiko; OKADA, Hironao; SAWADA, Hiroshi (Journal of Veterinary Medical Science, 2019)
We evaluated the relationship between ruminal motility measured by a force transducer and acceleration measured by bolus sensor, and we assessed the detection of ruminal motility in cattle by a bolus-type wireless sensor. The bolus sensor can be orally administered to cattle and was placed in the reticulum for continuous measurements. The probe was almost horizontal to the longitudinal axis. The bolus sensor’s basic y-axis acceleration movement appeared to have a very distinct vertical pattern, occurring roughly 1−1.5 times/min with a duration of approximately 8 sec, displaying at around 500 mG. A significant positive correlation was observed between the ruminal contraction revealed by the force transducer and the acceleration shown by the bolus sensor (P<0.01). The contraction of the dorsal sac of the rumen and the acceleration signals in the reticulum occurred at practically the same time. The frequency and amplitude of ruminal contraction demonstrated by the bolus sensor and the force transducer in feeding were significantly higher than those at rest (P<0.01). The bolus sensor could also detect ruminal atony in the cattle after the administration of xylazine. A bolus-type wireless sensor may thus be useful for the measurement of ruminal motility in cattle and for detecting rumen dysfunction (e.g., ruminal atony).